Making Safeguarding Personal: developing responses and enhancing skills. Issue 2 (8th April 2014) - Manthorpe, Jill; Klee, Deborah; Williams, Cathie; Cooper, Adi
Abstract : Purpose: – This paper aims to contextualise and summarise the Making Safeguarding Personal programme and to place this in the context of early developments in research-based evidence. Design/methodology/approach: – A programme of sector led improvement in local council adult safeguarding arrangements was carried out in four English local councils by the Local Government Association and other stakeholders. Support was provided to four local council test bed sites to assist them to test and adapt different approaches to adult safeguarding that placed emphasis on outcomes and on approaches to mediation to assist vulnerable adults to improve their circumstances. Findings: – Key findings from the test bed sites are that it may be possible to consider the outcomes of safeguarding interventions from "user" perspectives and that it appears that practitioners may welcome support with taking forward methods of mediation and work with family networks. These activities reflect an interest in developing practice responses and measures of effectiveness. Originality/value: – Councils will need to develop measures of the effectiveness of safeguarding arrangements and sector led improvements can contribute to these from a "bottom up" perspective. Practitioners often welcome opportunities to reflect on and to invest in responses to cases of alleged and proven abuse and neglect.